Panasonic Corporation / Wan Muhammad Syahmi Wan Azman - Wan Azman, Wan Muhammad Syahmi (2022)
Panasonic's brand slogan, "A Better Life, A Better World," aims to succinctly articulate the company's Basic Management Objective, which was founded by founder Konosuke Matsushita in the modern period. This Basic Management Objective reflects their mission and dedication, and it has served as the basis for all of their management practices as the core of their management philosophy. Recognizing their roles as industrialists, they would use their business practices to contribute to society's growth and prosperity, as well as people's well-being, thus improving the quality of life around the world. Only by the concerted efforts and collaboration of each employee of their organization will progress and growth be realized. They promise to fulfil their corporate duties with commitment, diligence, and dignity, united in spirit. Panasonic will continue to help address social problems and contribute to further growth in order to usher in a bright new future, based on its management philosophy.